Language Learning Strategies Among Vocational Generation Z Students: Insights from A Digital Native Perspective - Nidia Sofa; Fanny Puji Rakhmi; Iis Mariam; Mawarta Onida (Journal of English Language Studies, 2025)
This study explores the English language learning strategies employed by vocational Generation Z students at Politeknik Negeri Jakarta, focusing on their integration of digital-native characteristics within an English for Specific Purposes (ESP) context. Employing a quantitative survey design, data were collected from second-semester vocational students through two adapted instruments: Oxford’s Strategy Inventory for Language Learning (SILL) and Teo’s Digital Natives Assessment Scale (DNAS). A total of 108 students participated in the study. Data analysis revealed that students employed direct, indirect, and digital-native strategies at comparably high frequencies, with no statistically significant differences among the strategy types (p > 0.05). At the subscale level, instant gratification or rewards was most prominent, followed by metacognitive and technology use, whereas graphic communication was least used, with compensation and affective relatively lower. It is recommended that ESP educators should blend strategies within each task: begin with brief targeted language practice (direct), include a short plan/monitor step or peer check (indirect/metacognitive), and complete the task with approved digital support      in order to optimize ESP learning for vocational education contexts. Future work should validate the adapted digital-native scale in local contexts, replicate across diverse ESP settings, and link reported strategies to objective learning outcomes using longitudinal and mixed-methods designs.